2019
DOI: 10.1021/acs.langmuir.9b02841
|View full text |Cite
|
Sign up to set email alerts
|

Tensorial Modulation of Electrokinetic Streaming Potentials on Air and Liquid Filled Surfaces

Abstract: Textured surfaces, comprised of grooves filled with air, e.g., air-filled surfaces (AFS), or with liquid, e.g., liquidfilled surfaces (LFS), significantly influence fluid flows and the related electrokinetic streaming potential (V s ). Here, electroosmotic mobility related tensorial effects on the V s were experimentally investigated. A significant modulation of the V s , as high as 100%, due to transverse pressure gradients, was demonstrated. The study yields insights into understanding geometrical effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The orientational effects on such patterned surfaces manifested through a tensorial aspect to the developed V s were considered. 20,21 However, many issues related to what would be an ideal patterned surface for a given solid (/liquid) fraction in the LFS are still unclear. One major consideration is the optimization of the ζ•b product evident from the H−S relation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The orientational effects on such patterned surfaces manifested through a tensorial aspect to the developed V s were considered. 20,21 However, many issues related to what would be an ideal patterned surface for a given solid (/liquid) fraction in the LFS are still unclear. One major consideration is the optimization of the ζ•b product evident from the H−S relation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the given experimental conditions, L ∞ was at the mm scale, and it was assumed from such a consideration as well as from ESEM observations that the LFS are stable. 20,24 Streaming Potential (V s ) Measurement. The V s was monitored, on related pattern geometries in the microfluidics setup, using saltwater (with NaCl dissolved in water at a concentration of 0.1 mM) as an electrolyte.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oils were found to be immiscible with the aqueous electrolyte (NaCl in deionized to the grooves considering the robustness of the LFS, i.e., whether the filling liquid would experience drainage under external shear flow [38]. It was discussed previously that the filling liquid could be retained indefinitely in the grooves in such a configuration [39] and where the period (L) was less than a critical length [38]: 𝐿 ‡ , inversely proportional to the w/h ratio. Since, for the given conditions, 𝐿 ‡ was estimated to be of the order of millimeters, it was assumed, from such consideration as well from SEM observations after the experiments, Fig.…”
Section: (C)mentioning
confidence: 99%
“…It is observed that, in the comparison of batteries, unipolar transport through electric double layers in nanochannels may be coupled with liquid-infused surfaces to produce larger streaming potential. [46] In 2019, Wang et al reported a slippery lubricant-infused porous surface based on triboelectric nanogenerators, named as SLIPS-TENG, presenting configurability, optical transparency, self-cleaning, and power generation stability, in a wide range of working environmental temperatures from −3 to 25 °C. [47] Though in bending states, the SLIPS-TENG can still light up the LED bulb arrays on 200 nW.…”
Section: Liquid With Surfacesmentioning
confidence: 99%